FIORIN, José Luiz; FLORES, Valdir do Nascimento e BARBISAN, Leci Borges (orgs). Saussure: a invenção da Linguística. São Paulo: Contexto, 2013.174 p - Silva, Adriana Pucci Penteado de Faria e (Bakhtiniana. Revista de Estudos do Discurso, 2014)
Resenha